A Novel Robotic-Assisted Technique to Implant the Responsive Neurostimulation System. Issue 6 (19th September 2019) - Tran, Diem Kieu; Paff, Michelle; Mnatsakanyan, Lilit; Sen-Gupta, Indranil; Lin, Jack J; Hsu, Frank P K; Vadera, Sumeet
Abstract: BACKGROUND: The responsive neurostimulation system (RNS) (NeuroPace Inc, Mountain View, California) was approved as an adjunctive therapy for medically refractory focal epilepsy. RNS detects epileptiform patterns and delivers electrical stimulation to abort seizures. OBJECTIVE: To describe a novel technique of RNS lead implantation using robotic-assisted targeting of ictal-onset zones based on stereoelectroencephalography (sEEG) localization. Secondary objectives are to report the accuracy of robotic-assisted lead implantation using the ROSA robot as well as to report the clinical outcome achieved after RNS implantation by this method. METHODS: A total of 16 patients with medically refractory focal epilepsy underwent sEEG implantation for ictal-onset localization followed by robotic RNS implantation. The electrode most correlative with ictal onset on sEEG was chosen as the target for the RNS electrode. Seizure control was measured at 6-mo and 1-yr follow-up. Ictal-onset electrocorticography (ECoG) data from RNS were compared with ictal onset from sEEG leads based on calculations of lead target to actual lead location from the ROSA robot. RESULTS: At 6-mo follow-up, the average percent seizure reduction was 82% based upon self-reported seizure diaries. At 1-yr follow-up, 8 patients had an average of 90% seizure reduction. The location of seizure onset from ECoG data show similar onset from sEEG leads within 0.165-mm discrepancy. CONCLUSION: The ROSA robot provides an ideal method for targeting subcortical ictal-onset zones. This method of RNS lead implantation achieves high accuracy and is associated with favorable clinical outcomes.